Legitimasi Tradisi Lokal dalam Perspektif Hukum Islam: Analisis al-‘Urf terhadap Ritual Appalili’ pada Upacara Gaukang Karaeng Galesong di Kabupaten Takalar - Nurfadilah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The Appalili ritual in the Gaukang Karaeng Galesong ceremony in Takalar has social and spiritual values that serve to strengthen social cohesion and represent the relationship between customs and religion in the lives of the local Muslim community. However, the dynamics of modernity and globalization present challenges in the form of shifts in the legitimacy of local traditions and increasing demands for normative evaluation from an Islamic legal perspective. This study aims to analyze the legitimacy of the Appalili' ritual through the al-‘urf approach as an instrument for assessing Islamic law on local cultural practices. The research problem focuses on the normative values contained in the Appalili’ ritual and its position in the al-'urf categorization within the framework of Islamic law. This study uses qualitative methods with a normative theological and sociological approach to bridge the normative analysis of Sharia and the socio-cultural reality of society. Data was obtained from traditional leaders, religious leaders, and community leaders through participatory observation, in-depth interviews, and documentation, then analyzed systematically through descriptive-analytical, reduction, presentation, and data verification stages. The results of the study show that the Appalili ritual is carried out through a series of symbolic processes that do not contain elements of shirk, superstition, or violations of the principles of tawhid, so that normatively it can be classified as al-'urf saḥīḥ which has legitimacy in Islamic law. The novelty of this research lies in the development of an al-‘urf analytical framework as a normative evaluative instrument for traditional rituals, which simultaneously integrates an Islamic legal approach and sociological analysis and offers a conceptual model that can be replicated in studies of Muslim traditions in various cultural contexts. The implications of this research contribute to strengthening the discourse of contextual Islamic law, broadening the understanding of the relationship between sharia and local culture, and providing a theoretical basis for the preservation of religious traditions in line with Islamic principles in plural Muslim societies.